Enkapsulasi Ekstrak Daun Murbei untuk Peningkatan Absorpsi In-vitro Kandungan Rutin - Aminah, Siti (Indonesian Research Gateway)
The extract is a preparation that widely used of medicinal purposed plants. Rutin is an ingredient contained in the extract of mulberry leaves (Morus alba L.) and has very low solubility in water. Drugs with a low solubili ty will have dif????iculty in the process of absorption. In this study, chitosan is used for encapsulation formation of mulberry extract; furthermore, the encapsulated extract was then investigated the in- vitro absorption of the rutin. The extract was made using 95% ethanol by remaceration method. The encapsulation formulas consist of 0.25 % w/v mulberry extract, chitosan TPP mass ratio of 0.5:1 and of 1:1. The content of rutin in the extract was determined by using HPLC. Characterization was done on the particle size, zeta potential, encapsu-lation ef????iciency and FTIR. In-vitro absorptions of rutin in the mulberry leaves extract and of rutin in the encapsulated extract were carried out by Everted Small Intestine Sac Technique. The results showed that mulberry extract contains rutin as much as 0.879 ± 0.138 mg/g. Formulation with chitosan-TPP mass ratio of 0.5:1 and 1:1 formed par-ticles with sizes of 99.23±16.74 nm and 420.13± 30.52 nm, zeta potentials of 47.94±6.28 mV and -8.78± -1.36 mV, encapsulation ef????iciency of 76.14 ± 2.29 % and 59.06 ± 12.24 % respectively. Rutin absorption of the formulation with chitosan-TPP increased sig-ni????icantly (p< 0.05) as shown by increased their permeabilities. The absorption rate of rutin in the extract increased by encapsulation (p< 0.05).